Sosialisai dan Pendampingan HKI Peserta Krenova Kabupaten Jombang - Ali Mahsun; Anita Andriyani; Rudy Ananta; Novi Tri Hutomo (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Managing IPR ownership of copyrighted products is very urgent to do. IPR is a form of legal protection, valuable assets, and the economic value contained therein for individuals and groups. Apart from that, it can increase competitiveness and expand market share in aspects of commercialized intellectual property. The aim of this PKM activity is to increase the understanding of KRENOVA Jombang District participants about the importance of IPR and at the same time provide assistance in managing IPR. This activity uses several service stages, namely activity preparation, PKM team coordination, implementation, and collecting and proposing IPR files. This activity resulted in the issuance of IPR certificates for participants and increased participants' understanding of IPR.